Effect of In-Ovo Ascorbic Acid Injection on the Bone Development of Broiler Chickens Submitted to Heat Stress During Incubation and Rearing - Sgavioli, S. (2016)
This experiment was conducted to evaluate the effect of in-ovo ascorbic acid (AA) injection on the bone development of broilers submitted to heat stress during incubation and rearing. One thousand (1,000) Cobb (R) fertile broiler eggs were randomly distributed according to the weight into five incubators, with 200 eggs per incubator. The incubation treatments were: eggs not injected with AA and incubated at 37.5 degrees C; eggs not injected with AA and incubated at 39 degrees C; and eggs injected with 6 mu g AA/100 mu L water prior to incubation and incubated at 39 degrees C. The hatched birds were reared at three different house temperatures: cold, thermoneutral, or and hot. The high incubation temperature negatively influenced broilers' bone characteristics. The femur of the birds hatched from eggs incubated at 39 degrees C and injected with AA presented lower shaft mineral density, lower maximum force and lower elongation at maximum force. Their tibia presented reduced mineral density at the proximal and distal epiphysis. In-ovo AA injection of eggs incubated at high temperature did not minimize the negative effects of high rearing temperature on the performance andbone development of broiler chickens reared until 42 days of age.